PENGARUH ARUS LISTRIK TERHADAP KARAKTERISTIK FISIK-MEKANIK SAMBUNGAN LAS TITIK LOGAM DISSIMILAR AL-STEEL - Purwaningrum, Yustiasih; Fatchan, M. (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2013)
The resistance spot weld of dissimilar materials is generally more complex than that of similar materials due differences in the mechanical, physical and chemical properties of the base metals. This research aimed is to investigate the mechanical and physical properties of spot weld of dissimilar materials with various welding current. A Series of bead plate welds were made on 4 mm thick Al 5083 and 1,2 thick SS 400. The welding current that used were 65, 70 and 75 Amperes. The physical properties were examined based on the microstructure using Optical Microscope. The mechanical properties were measured with respect to the strength and hardness using Universal Testing Machine and Vickers Microhardness respectively. The microstructures of all resistance spot welded for carbon steel SS 400 with various welding current were bainit for weld metal and ferrite and pearlite for base metal and HAZ. Weld metal with current welding 75 A have the highest tensile-shear strength.